2002
DOI: 10.1016/s0002-9440(10)64353-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Host Desmoplastic Response to Pancreatic Carcinoma

Abstract: The dramatic opportunities presented by comprehensive gene profiling technologies are curbed by the problem of segregating these large amounts of gene expression data into meaningful categories for study. This is particularly evident in infiltrating carcinomas of the pancreas, in which global gene expression data primarily mirrors the prominent desmoplastic response to the infiltrating neoplasm. In an effort to better characterize the gene expression of invasive pancreatic cancers and their associated desmopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…This is the first study that has found that ApoC-1 is highly expressed in pancreatic cancer cells but is faintly expressed in normal pancreatic ductal and stromal cells that surround cancerous cells. These findings are supported by studies indicating that ApoC-1 mRNA was highly expressed in pancreatic cancer tissues based on the serial analysis of gene expression analysis (Ryu et al, 2001;Iacobuzio-Donahue et al, 2002). We also found that ApoC-1 was expressed in the supernatant of medium used to culture pancreatic cancer cells.…”
Section: Apoc-1prevents Apoptosis In Pancreatic Cancer S Takano Et Alsupporting
confidence: 88%
“…This is the first study that has found that ApoC-1 is highly expressed in pancreatic cancer cells but is faintly expressed in normal pancreatic ductal and stromal cells that surround cancerous cells. These findings are supported by studies indicating that ApoC-1 mRNA was highly expressed in pancreatic cancer tissues based on the serial analysis of gene expression analysis (Ryu et al, 2001;Iacobuzio-Donahue et al, 2002). We also found that ApoC-1 was expressed in the supernatant of medium used to culture pancreatic cancer cells.…”
Section: Apoc-1prevents Apoptosis In Pancreatic Cancer S Takano Et Alsupporting
confidence: 88%
“…Yasui et al [23] found that ApoC-I was up-regulated in gastric cancer cells compared with normal gastric epithelial cells, on the basis of serial analysis of gene expression (SAGE). Christine et al [24] performed in situ hybridization of pancreatic tissue to characterize the expression of ApoC-I genes identified by SAGE and found that ApoC-I was highly expressed in invasive pancreatic cancer tissues. On the basis of these results, ApoC-I expression seems to be regulated in several types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…These peaks, however, were not among the top 2-4 discriminating peaks. Pancreatic cancer induces increases in a variety of serum markers including proteins derived from the neoplastic cells such as CA19 -9, from surrounding acini (as in the case of HIP/PAP), as well as from surrounding stroma that could include inflammatory or matrix markers (25,32,33). These results suggest that in the future separate marker panels may be used depending on whether the clinical question is to determine whether a healthy individual has a pancreatic abnormality that may be nonspecific but that could indicate the presence of a subclinical cancer or if the clinical question being asked is to differentiate pancreatic cancer from inflammatory pancreatic conditions.…”
Section: Discussionmentioning
confidence: 99%